A multiscale theoretical approach for the sound absorption of slit-perforated double porosity materials. (1st September 2019) - Xin, Fengxian; Ma, Xiaowen; Liu, Xuewei; Zhang, Chuanzeng
Abstract: A multiscale theoretical approach is proposed to design the sound absorption of slit-perforated double porosity materials by employing the double porosity theory. The materials consist of a microporous matrix with periodically perforated narrow slits, in which the micropores of the matrix and the slits are interconnected and together form a multiscale material with double porosity. Considering the different ratios for the characteristic size of the micropores to that of the slits, two contrast cases including low permeability contrast (LPC) case and high permeability contrast (HPC) case are included in the design analysis. Numerical simulations based on COMSOL Multiphysics are conducted to verify the developed theoretical model, with good agreements being achieved. The comparison between the multiscale material and its two constituent elements manifests the superiority of the multiscale material for sound absorption. The analysis on the surface impedance and propagation constant exposes the fact that the multiscale material design improves the acoustic impedance matching between the material and air and leads to an enhancement of sound absorption. Furthermore, the effects of the multiscale parameters on the sound absorption of the double porosity materials are explored in terms of the distribution of the sound pressure and energy dissipation. This work provides a helpful guidance to improve the sound absorption of the microporous materials by employing the multiscale design approach.